APPLICATION OF MAGNETIC NANOPARTICLES FOR INTERFACIAL TENSION REDUCTION IN ENHANCED OIL RECOVERY - BAIG, MIRZA KHURRAM (2018)
The increasing demand for oil and gas has attracted the researchers to explore more efficient oil recovery methods. One technique that has received considerable concern and intensive study over these years is the use of magnetic nanoparticles based nano flooding instead of expensive surfactants.